Cārucarya - Anantam, 1919- (Ananta Sāhiti ; Śrī Vēṅkaṭēśvara Dhārmika Kēndramu, 1980)
Verse transcreation and commentary, with text, on Cārucaryā, treatise on moral precepts by Kṣemendra, 11th century Sanskrit poet and rhetorician.